Pengaruh Variasi Durasi Dan Kecepatan Sentrifugasi Terhadap Profil Telur Cacing Soil Transmitted Helminth Dalam Metode Sedimentasi - Benaya Yamin Onesiforus; Adi Kusuma (Universitas Muhamadiyah Manado, 2022)
Helminthiasis can be diagnosed by finding helminth eggs on a stool laboratory examination. Stool examination consists of qualitative and quantitative examination. One of the methods used in qualitative examination is the sedimentation method, this method utilizes the force of gravity by using a solution of lower density so that parasites can settle under the solution with the help of a centrifuge. One of the factors that affect centrifugation is time and speed. This study aims to determine the effect of time and speed of centrifugation on the profile of helminths eggs. The research was conducted at the meids laboratory of the Catholic Polytechnic Mangunwijaya Semarang. This type of research is experimental. Positive samples of Soil Transmitted Helminths (STH) eggs were centrifuged with time variations of 10 minutes, 5 minutes and 3 minutes at speeds of 3000 rpm, 2000 rpm and 1500 rpm. The data were then analyzed using Shapiro-wilk and Paired Samples T-test. Statistic test shows a difference of STH eggs profile between 3000 rpm 10 minutes and 2000 rpm 5 & 10 minutes, and 3000 rpm 3 & 5 minutes, between 2000 rpm 3 minutes and 1500 rpm 5 minutes, between 2000 rpm 10 minutes and 1500 rpm 5 minutes dan 200 rpm 3 minutes, between 3000 rpm 5 minutes and 2000 rpm 3 minutes (p < 0.05). There is an effect of variations in time and speed of centrifugation on the profile of STH eggs.